2001
DOI: 10.1051/0004-6361:20010270
|View full text |Cite
|
Sign up to set email alerts
|

Spiral arms in near-infrared bands

Abstract: Abstract.We investigate the contribution of Brγ and H2 emission due to young objects in the arms of spiral galaxies observed in the K filter. Out of a sample of disk galaxies for which we obtained deep surface photometry in broad-and narrow-band near-infrared filters, we selected two grand design spirals (NGC 5861, NGC 7412), which clearly have sharp knots along their arms both in optical and NIR images. For these galaxies we estimate the amount of light coming from Brγ and H2 emission and we conclude that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 10 publications
2
15
0
5
Order By: Relevance
“…In many cases these knots are embedded in dust lanes and invisible in visual bands. Taking advantage of the mutual alignment of eight of these knots along the southern arm of NGC 2997, Grosbøl et al (2006) obtained spectroscopy in the Jand K-bands detecting hydrogen Br γ in emission, undoubtedly demonstrating that the knots are HII regions deeply enshrouded in dust, confirming the results previously suggested by Patsis et al (2001). They also explored the relative position of the knots with respect to the ridge of the K-band arm to derive kinematic parameters of the density wave to constrain the star formation regime and ages of the knots.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…In many cases these knots are embedded in dust lanes and invisible in visual bands. Taking advantage of the mutual alignment of eight of these knots along the southern arm of NGC 2997, Grosbøl et al (2006) obtained spectroscopy in the Jand K-bands detecting hydrogen Br γ in emission, undoubtedly demonstrating that the knots are HII regions deeply enshrouded in dust, confirming the results previously suggested by Patsis et al (2001). They also explored the relative position of the knots with respect to the ridge of the K-band arm to derive kinematic parameters of the density wave to constrain the star formation regime and ages of the knots.…”
Section: Introductionsupporting
confidence: 81%
“…These points indicate that the knots are dynamically young. Patsis et al (2001) studied such knots in two galaxies using narrow-band filters in the K-band and concluded that the major contribution to their K-band fluxes comes from continuum radiation. In many cases these knots are embedded in dust lanes and invisible in visual bands.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the light from galaxies observed in K originates from an old stellar population, one frequently sees strings of very compact objects along the spiral arms (Patsis et al 2001). Their sizes and alignment suggest that they are young objects.…”
Section: Non-axisymmetric Perturbationsmentioning
confidence: 99%
“…In the case of M51, however, a recent study by Shetty et al (2007) shows that the observed density and velocity profiles across the disk do not obey the continuity equation in any frame rotating at a fixed angular speed. Also, the strength of spiral arms determined from K-band observations is prone to contamination by red supergiants in the arm regions (e.g., Rix & Rieke 1993;Patsis et al 2001). Given these observational uncertainties, it is desirable to run numerical simulations to pin down the arm parameters and thus access the connection between stellar arms and large-scale star formation in gaseous arms.…”
Section: Introductionmentioning
confidence: 99%